Exercise boost after surgery improves survival in model of metastatic breast cancer - Stagaard, Rikke; Jensen, Adina; Schauer, Tim; Bay, Marie Lund; Tavanez, Ana Rita; Wielsøe, Sabrina; Peletier, Merel; Strøbech, Jan Erik; Oria, Victor Oginga; Zornhagen, Kamilla Westarp; Albrechtsen, Reidar; Christensen, Jesper Frank; et al. (Frontiers in Immunology, 2025)
IntroductionDespite advances in breast cancer diagnosis and treatment of the primary tumor, metastatic breast cancer tumors remain largely incurable, and their growth is responsible for the majority of breast cancer-related deaths. There is therefore a critical need to identify ways to reduce metastatic tumor burden and increase breast cancer patient survival. While surgery and pharmacological treatments are the cornerstones of breast cancer intervention, epidemiological data suggests that physical activity can lower the risk of breast cancer development, improve adjuvant treatment tolerance, reduce the risk of disease recurrence and lower breast cancer-related death.MethodsIn this preclinical study, we set out to examine the impact of exercise on metastatic development in triple negative breast cancer (TNBC), using different 4T1 metastasis models, voluntary wheel running and surgical interventions. Tumors were analyzed for hypoxia and immune cell infiltration.ResultsVoluntary wheel running was observed to significantly increase metastasis-free survival, doubling the median survival time. However, these improvements were only observed when a boost in physical exercise occurred following surgery. To investigate this, we performed mock surgeries and confirmed surgical stress was needed to enable the positive effects of the boost in exercise on reducing metastatic tumor burden in mice with either spontaneous metastasis or experimentally-induced metastasis. These changes occurred in the absence of alterations in tumor growth, hypoxia and immune cell infiltration.DiscussionTaken together, our results suggest that having a boost of physical activity following surgery may be beneficial to delay breast cancer metastatic development.